The Effect of Work Climate and Motivation Towards Teachers’ Performance in Teaching and Learning Process - Tauchida, Dian; Arofik (Tadibia Islamika: Journal of Holistic Islamic Education, 2021)
This quantitative research investigates the influence of work climate and work motivation on teacher success and their impact on educational practices. It utilizes multiple linear regression to determine whether these factors, individually or combined, significantly affect teacher performance in the teaching and learning process. Data collection involves surveys and interviews, with SPSS used for data analysis, including validity, reliability, and hypothesis testing. The study reveals the following key findings: Firstly, the work climate significantly affects teacher performance in teaching and learning, with a significance value (X1) of 0.025, supporting the alternative hypothesis (Ha) and rejecting the null hypothesis (Ho). The t-count value for the work climate variable, 2.394, exceeds the t-table value of 2.069, highlighting its substantial impact. Secondly, motivation significantly influences teacher performance in teaching and learning, with a significance level of 0.007, surpassing 0.05. The t-test result for motivation, 2.992, is higher than the t-table value of 2.069, confirming Ha and rejecting Ho. Finally, both work climate and motivation collectively impact teacher performance in teaching and learning, with an F-statistic of 8.519, surpassing the F-table value of 3.40. This is confirmed by a significance level of 0.002, less than 0.05, supporting Ha and rejecting Ho. In conclusion, work climate and motivation jointly shape teacher performance in the teaching and learning process.